Extração de quitina e quitosana de escamas de pirarucu (Arapaima gigas) - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Fish residues are not disposable materials with no nutritional value, but they prove to be an excellent raw material for the extraction of various compounds. The pirarucu (Arapaima gigas) scales carry in their composition, in addition to protein and mineral compounds, a reasonable volume of good quality chitin and chitosan that can be exploited for application in various industrial, technological, medical and other branches. The objective of this work was to extract, determine the yield and characterize chitin and chitosan obtained from pirarucu scales. The pirarucu scale samples were submitted to two treatments, T1 being homogeneous extraction, an adaptation of the process with the samples resting for 24 hours in solution before the application of heat, and T2 heterogeneous extraction, with direct application of the samples in chemical solution under heating. The analysis of Fourier Transform Infrared Region Spectroscopy (FTIR) showed signature of the relative bands of chitin and chitosan. The chitins T1 and T2 and chitosan T1 and T2 obtained from the processes showed distinct characteristics, where the extracted chitins presented volumes of about 1.37% (±0.30) and 38.84% (±4.40) for T1 and T2, respectively, while chitosans showed values around 84.68% (±6.99) and 76.66% (±5.58) for T1 and T2, respectively. The proximate composition of scales and carbohydrate polymers were also evaluated. The scales, chitin and chitosan presented mean values of 20.53% (±2.23), 11.49% (±0.59) and 6.91% (±0.30), for moisture and 0.07% (±0.01), 0.05% (±0.01), 1.08% (±0.47) for lipids; The protein showed values around 36.13% (±2.13), 1.01% (±0.34), 0.51% (±0.34); Ash presented estimated values of 31.16% (±0.62), 80.71% (±0.17) and 75.76% (±0.13). The pirarucu scales are a source of chitin and chitosan biomolecules, with great potential for technological applications.
Keywords: Pirarucu (Peixe) - Amazônia; Peixe de água doce; Pesca - Produtos; CIENCIAS AGRARIAS: RECURSOS PESQUEIROS E ENGENHARIA DE PESCA; Polímeros carboidratos; Estruturas calcificadas em peixes; N-Acetil; Subproduto de pescado